Path Analysis of Adoption of Improved Agricultural Package of Practices by Project Affected Farmers - Umesh R. Chinchmalatpure,; V. V. Mayani, (Journal of Agricultural Extension Management, 2014)
The rehabilitation and resettlement of the affected population of the Sardar Sarovur Project (SSP) has become a sensitive issue and has been given the highest priority in its implementation. A rehabilitation policy has been formulated by the Government of Gujarat. The primary objective of which is to significantly improve the economic condition of the Project Affected Farmers (PAFs) after resettlement. At the rehabilitated location, PA.Fs are cultivating different crops. The present study has designed to measure the extent of adoption of recommended practices and find out the variables influencing the adoption of practices by Sardar Sarovur Project Affected Farmers.